Species limits, geographical distribution and genetic diversity in Johannesteijsmannia (Arecaceae). (25th August 2016) - Bacon, Christine D.; Look, Su Lee; Gutiérrez–Pinto, Natalia; Antonelli, Alexandre; Tan, Hugh T. W.; Kumar, Prakash P.; Guan, Saw Leng; Dransfield, John; Baker, William J.
Abstract : Four species are recognized in the understorey palm genus Johannesteijsmannia (Arecaceae), all of which occur in close geographical proximity in the Malay Peninsula. We hypothesize that overlapping distributions are maintained by a lack of gene flow among species and that segregation along morphological trait or environmental axes confers ecological divergence and, hence, defines species limits. Although some species have sympatric distributions, differentiation was detected among species in morphological and genetic data, corroborating current species delimitation. Differences in niche breadth were not found to explain the overlapping distribution and co‐existence of Johannesteijsmannia spp. Four species formed over the last 3 Mya, showing that diversity accumulated within a short time frame and wide range expansion has not occurred, potentially due to a lack of time for dispersal or the evolution of traits to facilitate movement. An assessment of genetic diversity is presented and, as expected, the widest distribution in the genus harbours the highest genetic diversity.